EFEK ANTIBAKTERI BUAH MENGKUDU (Morinda citrifolia) TERHADAP PERTUMBUHAN Aeromonas hydrophila - Mulia, Dini Siswani; Silfiana, Kartika; Sumardi, Eddy (Universitas Muhammadiyah Purwokerto, 2008)
The research was carried out with the experiment method, to look for the value of Minimal Inhibitory Concentration (MIC or KHM) and LD50.The MIC determination was carried out in two stages. Firstly, it determined the dose of the concentration 0, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 mg/ml.Â The research showed that MIC was found 16,8 mg/ml and for determining of LD50 was continously decided by up to dose 16.8; 17.0; 17.2; 17.4; 17.6 mg/ml with 10 replication. MICâs data analyzed with Completely Randomize Design with 9 treatment and 5 replication. The analysies used F test and than BNT with 5 % significantly. Results of the research showed the treatment of the dose 16.6 mg/ml could inhibite the A. hydrophila growth with the diameter in general as big as 0.72 mm,.whereas on the LD50 the consentration revealed 16.8 mg/ml.Â